Differential diagnosis of squamous cell carcinoma in situ using skin histopathological images. (1st March 2016) - Noroozi, Navid; Zakerolhosseini, Ali
Abstract: Differential diagnosis of squamous cell carcinoma in situ is of great importance for prognosis and decision making in the disease treatment procedure. Currently, differential diagnosis is done by pathologists based on examination of the histopathological slides under the microscope, which is time consuming and prone to inter and intra observer variability. In this paper, we have proposed an automated method for differential diagnosis of SCC in situ from actinic keratosis, which is known to be a precursor of squamous cell carcinoma. The process begins with epidermis segmentation and cornified layer removal. Then, epidermis axis is specified using the paths in its skeleton and the granular layer is removed via connected components analysis. Finally, diagnosis is done based on the classification result of intensity profiles extracted from lines perpendicular to the epidermis axis. The results of the study are in agreement with the gold standards provided by expert pathologists. Highlights: A method for computer assisted diagnosis of squamous cell carcinoma in situ is presented. The method provides the pathologists a second consultative opinion in evaluating histopathological samples. In this algorithm, active contours, connected component analysis and sample-frequency distribution are used for recognition. The results of the study are in agreement with the gold standards provided by expert pathologists.